In-Silico Study of Brassinosteroid Signaling Genes in Rice Provides Insight Into Mechanisms Which Regulate Their Expression - Ahmar, Sunny; Gruszka, Damian (Frontiers in Genetics, 2022)
Brassinosteroids (BRs) regulate a diverse spectrum of processes during plant growth and development and modulate plant physiology in response to environmental fluctuations and stress factors. Thus, the BR signaling regulators have the potential to be targeted for gene editing to optimize the architecture of plants and make them more resilient to environmental stress. Our understanding of the BR signaling mechanism in monocot crop species is limited compared to our knowledge of this process accumulated in the model dicot species - Arabidopsis thaliana. A deeper understanding of the BR signaling and response during plant growth and adaptation to continually changing environmental conditions will provide insight into mechanisms that govern the coordinated expression of the BR signaling genes in rice (Oryza sativa) which is a model for cereal crops. Therefore, in this study a comprehensive and detailed in silico analysis of promoter sequences of rice BR signaling genes was performed. Moreover, expression profiles of these genes during various developmental stages and reactions to several stress conditions were analyzed. Additionally, a model of interactions between the encoded proteins was also established. The obtained results revealed that promoters of the 39 BR signaling genes are involved in various regulatory mechanisms and interdependent processes that influence growth, development, and stress response in rice. Different transcription factor-binding sites and cis-regulatory elements in the gene promoters were identified which are involved in regulation of the genes’ expression during plant development and reactions to stress conditions. The in-silico analysis of BR signaling genes in O. sativa provides information about mechanisms which regulate the coordinated expression of these genes during rice development and in response to other phytohormones and environmental factors. Since rice is both an important crop and the model species for other cereals, this information may be important for understanding the regulatory mechanisms that modulate the BR signaling in monocot species. It can also provide new ways for the plant genetic engineering technology by providing novel potential targets, either cis-elements or transcriptional factors, to create elite genotypes with desirable traits.